Adenosine, lidocaine and Mg2+ update: teaching old drugs new tricks - Dobson, Geoffrey P.; Morris, Jodie L.; Letson, Hayley L. (Frontiers in Medicine, 2023)
If a trauma (or infection) exceeds the body’s evolutionary design limits, a stress response is activated to quickly restore homeostasis. However, when the injury severity score is high, death is often imminent. The goal of this review is to provide an update on the effect of small-volume adenosine, lidocaine and Mg2+ (ALM) therapy on increasing survival and blunting secondary injury after non-compressible hemorrhagic shock and other trauma and infective/endotoxemic states. Two standout features of ALM therapy are: (1) resuscitation occurs at permissive hypotensive blood pressures (MAPs 50–60 mmHg), and (2) the drug confers neuroprotection at these low pressures. The therapy appears to reset the body’s baroreflex to produce a high-flow, hypotensive, vasodilatory state with maintained tissue O2 delivery. Whole body ALM protection appears to be afforded by NO synthesis-dependent pathways and shifting central nervous system (CNS) control from sympathetic to parasympathetic dominance, resulting in improved cardiovascular function, reduced immune activation and inflammation, correction of coagulopathy, restoration of endothelial glycocalyx, and reduced energy demand and mitochondrial oxidative stress. Recently, independent studies have shown ALM may also be useful for stroke, muscle trauma, and as an adjunct to Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). Ongoing studies have further shown ALM may have utility for burn polytrauma, damage control surgery and orthopedic surgery. Lastly, we discuss the clinical applications of ALM fluid therapy for prehospital and military far-forward use for non-compressible hemorrhage and traumatic brain injury (TBI).